2009
DOI: 10.1063/1.3156029
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependent emission properties of columnar quantum dash laser structures

Abstract: Hein, S.; Podemski, P.; Sek, G.; Misiewicz, J.; Ridha, P.; Fiore, A.; Patriarche, G.; Höfling, S.; Forchel, A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…This was attributed to the addition of light-hole contributions into the primarily heavy-hole transitions in these Qdashes. This study was further supported by Hein et al [189] and Podemski et al [187] via columnar Qdashes growth, stating a strong relationship between the polarization degree of emission and the orientation of the columnar Qdashes. Besides the above findings, Popescu et al [192] showed that geometrical asymmetry of Qdashes influences the carrier migration (ambipolar carrier migration length), and noticed a 20% reduction in carrier migration along Qdash elongation compared to that across the dash elongation (i.e.…”
Section: Qdash Optical Propertiessupporting
confidence: 68%
See 1 more Smart Citation
“…This was attributed to the addition of light-hole contributions into the primarily heavy-hole transitions in these Qdashes. This study was further supported by Hein et al [189] and Podemski et al [187] via columnar Qdashes growth, stating a strong relationship between the polarization degree of emission and the orientation of the columnar Qdashes. Besides the above findings, Popescu et al [192] showed that geometrical asymmetry of Qdashes influences the carrier migration (ambipolar carrier migration length), and noticed a 20% reduction in carrier migration along Qdash elongation compared to that across the dash elongation (i.e.…”
Section: Qdash Optical Propertiessupporting
confidence: 68%
“…In general, these findings were attributed to the increase in Qdash vertical dimensions when PL intensity from the cleaved facet edge perpendicular to the columnar dashes longer lateral size was acquired. However, emission from the other edge (parallel to the Qdashes' longer lateral size) did not show any dependence of polarization on the dash height since the polarization was driven by the dashes longer lateral size rather than height [189]. A more detailed and systematic investigation of the Qdash height on the polarization of the surface emission was carried out by Musial et al [190] who showed through surface PL emission from these dashes was primarily driven by Qdash height due to heavy hole and light hole mixing.…”
Section: Qdashes On (100) Inp Substratementioning
confidence: 99%
“…They are dependent on only one parameter which is exciton to biexciton lifetimes ratio τ X /τ XX , which is typically assumed to be 2 (for the systems where the internal exciton relaxation from the bright to the dark states related with the spin flip is slow [19]). Figure 7 shows the dependence of the C and D lines intensity on the excitation power fitted by the theoretical relations (7) and (8). The obtained agreement (the model could not fit line D with any of the other observed lines, i.e.…”
Section: Photoluminescence From a Single Inas/inp Quantum Dashmentioning
confidence: 84%
“…1. All of them can be grown by molecular beam epitaxy and their growth parameters have been presented elsewhere [1,[6][7][8][9]. The structural characterization revealed that the InAs quantum dashes grown on InP substrate are usually more than 100 nm long, whereas their dimensions in the cross-section (perpendicular to the largest size), shape of which can be well modeled by a triangle, are directly correlated (and hence well controlled) with the amount of the deposited InAs material [10] and of the order of 10-30 nm in base width and several nm in height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation